Where do we go from here? A bibliometric analysis identifying implications for future research in Circular Economy and Supply Chain Management - Marcel Papert; Daniel Reich; Isabel Fischer; Thomas Goertler (Logistics Research, 2024)
The Circular Economy (CE) relies heavily on Supply Chain Management (SCM) as it involves managing the entire value chain and coordinating flows. Despite significant contributions, research on SCM for CE remains fragmented, which hinders a comprehensive exploration. This study presents a bibliometric analysis of 281 publications to examine the intersection between CE and SCM. The main research topics are identified and future directions are suggested. The findings contribute to the literature on CE and SCM by providing a comprehensive overview of the current state of knowledge and the barriers. Valuable implications for future research directions are also provided. Additionally, the implications can guide practitioners, institutions, and policymakers in shaping their SCM strategies and contributing to the ongoing transition to a CE.
Keywords: 650; circular economy; Supply chain management; bibliometric analysis; literature review; vosviewer